2016
DOI: 10.4103/2231-0762.183113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of palatal rugae shapes in Karnataka and Kerala population: A cross-sectional study

Abstract: Aims and Objectives:This study was conducted to assess the incidence and prevalence of palatal rugae shapes in the male and female populations of Karnataka and Kerala.Materials and Methods:This study consisted of 100 plaster models of each group, which were equally distributed between both the genders, with an age range of 17–23 years. The rugae patterns were recorded by using Thomas and Kotze classification. Correlation between the rugae shape and population as well as the rugae shape and gender were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Kapali and colleagues [ 19 ] studied the pattern of palatal rugae in Australian Aborigines and Caucasians and observed the number, length, shape, direction and unification of the rugae. Several studies have shown a significant association between rugae forms and ethnicity [ 1 , 2 , 17 – 27 , 29 31 , 37 ]. Due to the variation of the rugae pattern in different ethnicities, there is a need to provide information on the distal extent of the rugae in the Jordanian population.…”
Section: Introductionmentioning
confidence: 99%
“…Kapali and colleagues [ 19 ] studied the pattern of palatal rugae in Australian Aborigines and Caucasians and observed the number, length, shape, direction and unification of the rugae. Several studies have shown a significant association between rugae forms and ethnicity [ 1 , 2 , 17 – 27 , 29 31 , 37 ]. Due to the variation of the rugae pattern in different ethnicities, there is a need to provide information on the distal extent of the rugae in the Jordanian population.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by curved, straight and unification pattern of rugae. Study by J K Savitha et al 23 has seen similar results where curved rugae were more prominent in Kerala population as compared to Karnataka population. Horizontal rugae alignment and droplet-shaped incisive papilla was identified among all three skeletal dysplasia groups.The study by Ekrem Oral et al 10 also reported droplet-shaped incisive papilla to be the most common type in Turkish population.…”
Section: Table 2: Chi Square Test Showing the Shape Of The Incisive Papilla Among The Groups Discussionmentioning
confidence: 58%
“…According to Thomas 1983, palatal rugae do not undergo any changes except in length, throughout a person's life probably due to underlying growth. 11 Comparative studies performed amongst geographically diverse populations belonging to Indian regions such as Karnataka and Kerala 23 and Manipur and Kerala 5 , have demonstrated important differences in rugae pattern. A study comparing two groups of Indian population (southern Indians and western Indians) predominantly showed the prevalence of wavy and curved rugae forms followed by straight rugae pattern.…”
Section: Table 2: Chi Square Test Showing the Shape Of The Incisive Papilla Among The Groups Discussionmentioning
confidence: 99%
“…The mean dimensions of males were higher than the females in Kerala city whereas in Karnata city, females possessed the higher dimensions than males. 11 Similarly, Pappu BT calculated the individual length of rugae and explored a higher mean length of rugae in males (5.96±0.64) than in females (4.28±0.34). 12 This may be due to a vast disparity seen in the methodology in calculating the palatal rugae dimensions by different investigators.…”
Section: Discussionmentioning
confidence: 99%